A high-strength double network polydopamine nanocomposite hydrogel for adhesion under seawater. Issue 36 (15th July 2020) - Liang, Min; He, Chunpeng; Dai, Jidong; Ren, Pengfei; Fu, Yifu; Wang, Faming; Ge, Xin; Zhang, Tianzhu; Lu, Zuhong
Abstract : A mussel-inspired catechol-based strategy has been widely used in the development of underwater adhesives. Abstract : Mussel-inspired catechol-based strategy has been widely used in the development of underwater adhesives. Nonetheless, the properties of the adhesives were still severely limited under harsh environments. A facile approach was proposed herein to prepare a double network hydrogel adhesive with low swelling rate and high strength in seawater, where the first network was polyacrylamide (PAM) and the second network was alginate (Alg). Meanwhile, polydopamine (PDA) nanoparticles, which were formed through self-polymerization as adhesion anchoring sites, distributed evenly throughout the double network hydrogel and effectively enhanced the adhesion capability of the hydrogel. The properties of the resulting hydrogel have been fully characterized. The optimal adhesion strength of the hydrogel adhesive in seawater was as high as 146.84 ± 7.78 kPa. Furthermore, the hydrogel also has excellent ability to promote the growth of zooxanthellae. Our studies provide useful insights into the rational design of underwater adhesives with high performances even beyond nature.